2016
DOI: 10.1590/1807-1929/agriambi.v20n6p570-575
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of enthalpy in broiler house during the heating phase

Abstract: A B S T R A C TThe thermal environment inside a broiler house has a great influence on animal welfare and productivity during the production phase. Enthalpy is a thermodynamic property that has been proposed to evaluate the internal broiler house environment, for being an indicator of the amount of energy contained in a mixture of water vapor and dry air. Therefore, this study aimed to characterize the spatial variability of enthalpy in a broiler house during the heating phase using geostatistics. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The reach values concerning the semivariograms are relevant in determining the spatial dependence limit. They indicate the sampling limit distance in which the collected points are spatially correlated (Ferraz et al 2016). The highest values of t db range during the summer referred to the dawn period (summer), with a range of 51.035 m, and in the winter during the afternoon, with a range of 34.685 m. For RH, the highest reach values referred to the morning in the summer and during the afternoon and night in the winter, with a reach of 36.141 m, 30.240 m, and 30.240 m, respectively.…”
Section: Geostatistical Analysismentioning
confidence: 99%
“…The reach values concerning the semivariograms are relevant in determining the spatial dependence limit. They indicate the sampling limit distance in which the collected points are spatially correlated (Ferraz et al 2016). The highest values of t db range during the summer referred to the dawn period (summer), with a range of 51.035 m, and in the winter during the afternoon, with a range of 34.685 m. For RH, the highest reach values referred to the morning in the summer and during the afternoon and night in the winter, with a reach of 36.141 m, 30.240 m, and 30.240 m, respectively.…”
Section: Geostatistical Analysismentioning
confidence: 99%
“…Recent experimental approaches to evaluate thermal comfort in broilers include: the use of thermal imaging (Nascimento et al, 2014) associated with the usual/typical variables, but requires high-cost measuring instruments and no records in real-time; obtaining thermal maps via real-time environment monitoring using 50 temperature sensors and 18 6. Temperature (left) and airflow speed (right), numerical (top) versus experimental (bottom); Boundary condition -Heat flux (q'' = 81.8 W m -2 ) and airflow (m = 9.7 kg s -1 ; P outlet = 30 Pa) for RH (Coelho et al, 2015); thermography for animal health (footpad dermatitis) enabling diagnosis of not visible injuries (Jacob et al, 2016); enthalpy mapping in poultry barns (Ferraz et al, 2016); use of LED -light emitting diodes to improve energy efficiency, i.e., lower electricity consumption, in aviaries (Thomson & Corscadden, 2018); CFD flow simulation for ventilation systems evaluation in poultry barns (Curi et al, 2017); development and construction of PIC microcontroller (Peripherical Interface Controller) for variables supervision and control via commercial software and hardware (Proteus ISI Professional v.8 and MATLAB v. 7.8) (Alecrim et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…They were the nugget effect (C 0 ), sill (C 0 + C 1 ) and range of influence (a). Ferraz et al (2016Ferraz et al ( , 2020 and Ribeiro et al ( 2016) studied the spatial distribution in animal facilities and concluded that the spherical model had the best fit, because of its relatively easy ability to adjust to any cloud point. The method of Restricted Maximum Likelihood (REML) was employed to fit the data, because it allowed a less biased estimate for small data cluster (Marchant & Lark 2007).…”
Section: Geostatistical Analysismentioning
confidence: 99%